The Catholic Church, Jews, the Shoah and the State of Israel: Interpretations and responses - Havel, Boris (Nordisk judaistik/Scandinavian Jewish Studies, 2023)
Judaism and Christianity are religions whose theological epistemology is based on revelation. The primary source of revelation is Holy Scripture. However, history has also been recognised as a source of revelation, particularly the history of Israel and the Jewish people. Because they understood history as a source of revelation, many religious Jews altered their understanding of Jewish statehood in Eretz Israel during the twentieth century, from distinctly averse to increasingly supportive. On the same principles, the Catholic Church made arguably the most profound change in its theology in the twentieth century, concerning its understanding of Jews and Judaism. This was prompted by another major historical event, the Shoah. While in Judaism the historical phenomenon of the State of Israel profoundly influenced theology, another historical phenomenon, the Shoah, was theologically approached with far more unease and ambiguity. In the Catholic Church, in contrast, the historical phenomenon of the Shoah prompted a serious reconsideration of certain tenets of theology, including soteriology, while the historical phenomenon of the State of Israel did not. This article addresses this apparent contradiction comparatively.